Proceedings of the International Symposium on Mechanical Engineering and Material Science 2016
DOI: 10.2991/ismems-16.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Microstructure of AA2219 Friction Stir Welded Joint

Abstract: Abstract. Friction Stir Welding (FSW) is an environment friendly solid-state joining technology that uses a rotating tool to generate frictional heat and plastic deformation with mixing of the soft material by the pin along the welding line. The advantages are low distortion, lack of traditional defects commonly found in fusion welds and high joint efficiency. The paper focuses on microstructure evolved after welding and the effect of welding process is discussed for aluminum alloy 2219. This alloy is selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…From the previous experimental and modeling research, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][23][24][25][26][27][28][29] it is known that the welding parameters affect important variables such as temperature, strain rate, torque, and maximum shear stress on the tool pin that affect properties of the plasticized alloy and its smooth flow. Since the disruption of the smooth flow is thought to cause the void formation, the values of these four variables are important for the void formation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the previous experimental and modeling research, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][23][24][25][26][27][28][29] it is known that the welding parameters affect important variables such as temperature, strain rate, torque, and maximum shear stress on the tool pin that affect properties of the plasticized alloy and its smooth flow. Since the disruption of the smooth flow is thought to cause the void formation, the values of these four variables are important for the void formation.…”
Section: Resultsmentioning
confidence: 99%
“…Efforts have been made to experimentally determine the effects of welding parameters on void formation in commonly used aluminum alloys. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Tracers have been used to examine experimentally how the flow of materials affect the void formation. [20][21][22] The time lapse determination of the tracer's position in some cases indicated that the voids occurred near the bottom of the pin where the flow of the plasticized material was interrupted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation